PANCREATICODUODENECTOMY WITH VENOUS RESECTION: AN ANALYSIS OF 30-DAY MORBIDITY AND MORTALITY - CALLEJAS,Guilherme Hoverter (2019)
ABSTRACT BACKGROUND: Pancreaticoduodenectomy (PD) with the resection of venous structures adjacent to the pancreatic head, even in cases of extensive invasion, has been practiced in recent years, but its perioperative morbidity and mortality are not completely determined. OBJECTIVE: To describe the perioperative outcomes of PD with venous resections performed at a tertiary university hospital. METHODS: A retrospective study was conducted, classified as a historical cohort, enrolling 39 individuals which underwent PD with venous resection from 2000 through 2016. Preoperative demographic, clinical and anthropometric variables were assessed and the main outcomes studied were 30-day morbidity and mortality. RESULTS: The median age was 62.5 years (IQ 54-68); 55% were male. The main etiology identified was ductal adenocarcinoma of the pancreas (82.1%). In 51.3% of cases, the portal vein was resected; in 35.9%, the superior mesenteric vein was resected and in the other 12.8%, the splenomesenteric junction. Regarding the complications, 48.7% of the patients presented some type of morbidity in 30 days. None of the variables analyzed was associated with higher morbidity. Perioperative mortality was 15.4% (six patients). The group of individuals who died within 30 days presented significantly higher values for both ASA (P=0.003) and ECOG (P=0.001) scores. CONCLUSION: PD with venous resection for advanced pancreatic neoplasms is a feasible procedure, but associated with high rates of morbidity and mortality; higher ASA e ECOG scores were significantly associated with a higher 30-day mortality.